Okoljska in razvojna vloga kmetijstva v Mestni občini Ljubljana - Lampič, Barbara (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
The article deals with the results of a survey concerning the evaluation of agriculture and its environmental role. Special emphasis is placed on the extent and types of agriculture burdening, as well as perspectives in agriculture in the greater Ljubljana area. The diversity of landscape in municipality has significant influence on the orientation and functions of agriculture, and on the present and future land use. Over the last decade, there has been a significant decline in the number of active farms, although the trend is gradually slowing down. It is anticipated that the number of the currently 600 active farms will decrease by a further 20 - 30%, and their structure and size will also change.
Keywords: Ljubljana; urbana geografija; raba tal; agriculture; kmetijstvo; obremenjevanje okolja; onesnaževanje; environmental protection; varstvo okolja; ekološko ravnotežje; sustainable development; trajnostni razvoj